2018
DOI: 10.1002/tox.22622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aloe emodin on U87MG glioblastoma cell growth: In vitro and in vivo study

Abstract: Glioblastoma, the most aggressive and malignant form of glioma, appears to be resistant to various chemotherapeutic agents. Hence other approaches have been investigated to target more pathways involved in glioblastoma development and progression. Here we investigate the anticancer effect of Aloe-Emodin (AE), an anthraquinone compound presents in the leaves of Aloe arborescens, on human glioblastoma cell line U87MG. U87MG were treated with various concentrations of AE (20 and 40 μM) for different times (24, 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…α-Bisabolol, which is a natural compound strongly inducing apoptosis in glioma cells [2], or β-Elemene, i.e., a natural plant drug obtained from Curcuma wenyujin inducing apoptosis in glioblastoma cells, exert promising anticancer effects against a broad spectrum of tumors [32,67]. Another example of molecules characterized by an anticancer effect on human glioblastoma cell line U87MG is aloe emodin, i.e., an anthraquinone compound present in the leaves of Aloe arborescens, and hispolon, which is a polyphenolic compound isolated from Phellinus linteus [68]. The study presented in this paper is the first attempt to search for phytochemicals contained in Arnica rhizomes and roots characterized by antiglioma activity.…”
Section: Discussionmentioning
confidence: 99%
“…α-Bisabolol, which is a natural compound strongly inducing apoptosis in glioma cells [2], or β-Elemene, i.e., a natural plant drug obtained from Curcuma wenyujin inducing apoptosis in glioblastoma cells, exert promising anticancer effects against a broad spectrum of tumors [32,67]. Another example of molecules characterized by an anticancer effect on human glioblastoma cell line U87MG is aloe emodin, i.e., an anthraquinone compound present in the leaves of Aloe arborescens, and hispolon, which is a polyphenolic compound isolated from Phellinus linteus [68]. The study presented in this paper is the first attempt to search for phytochemicals contained in Arnica rhizomes and roots characterized by antiglioma activity.…”
Section: Discussionmentioning
confidence: 99%
“…Aloe-emodin in aloe vera, 6-gingerol in ginger and piperine in black pepper are all reported to inhibit tumor invasion and metastasis through the suppression of expression of matrix metalloproteinase-2/9 (38,42). All ingredients of BU, except epsom salts, have been revealed to exert apoptotic activity in various cancer cell lines, including SMMC-7721 (56), a human glioblastoma cell line (U87MG) (57), prostate cancer (58), H460 non-small cell lung carcinoma (59), adriamycin-resistant human leukemia (K562/ADR) (60), MCF-7 (61), IOMM-Lee and CH157MN (62) via the overexpression of BCL2 associated X, apoptosis regulator (60)(61)(62), caspase 3 (57,62), caspase 8 (57), caspase 9 (59), induced ROS accumulation (56,61) or via the AKT/mitogen-activated protein kinase pathway (60).…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor effects of rhubarb anthraquinones are mainly focused on the inhibition of brain tumor growth by inducing apoptosis[10, 55–58]. Plenty of in vitro studies have shown danthron can inhibit glioma growth[10, 55–57], which is a brain tumor with poor prognosis and usually develops into high-grade malignancies[15, 59].…”
Section: Neuroprotective Effects Of Anthraquinones From Rhubarb Inmentioning
confidence: 99%